2020
DOI: 10.1542/peds.2019-2465
|View full text |Cite
|
Sign up to set email alerts
|

State Variation in Posthospital Home Nursing for Commercially Insured Medically Complex Children

Abstract: BACKGROUND AND OBJECTIVES: Home nursing is essential for children with medical complexity (CMC), but provision varies substantially across states. Our objectives were to quantify state-to-state variability in distribution of posthospitalization home nursing to commercially insured CMC and to rank-order states.METHODS: Retrospective cohort study of hospitalized commercially insured children with $1 complex chronic condition from birth to 18 years of age in the Truven MarketScan database. Cohort eligibility crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…48 Another retrospective cohort evaluation of 88,139 commercially insured children, found that the adjusted probability of receiving post-hospitalization home nursing within 30 days varied substantially across states (3.4%-19.2%). 53 Studies also evaluated home healthcare access through the lens of hospital discharge delays. 23,25,27,34,38,47,50,[54][55][56][57] The most methodologically rigorous study was a multi-site prospective cohort study of 185 patients found that inadequate home healthcare nursing accounted for an average excess stay in the hospital of 53.9 days (range: 4-204) and 35.7 days (3-6) for new and existing patients, respectively.…”
Section: Results Synthesismentioning
confidence: 99%
“…48 Another retrospective cohort evaluation of 88,139 commercially insured children, found that the adjusted probability of receiving post-hospitalization home nursing within 30 days varied substantially across states (3.4%-19.2%). 53 Studies also evaluated home healthcare access through the lens of hospital discharge delays. 23,25,27,34,38,47,50,[54][55][56][57] The most methodologically rigorous study was a multi-site prospective cohort study of 185 patients found that inadequate home healthcare nursing accounted for an average excess stay in the hospital of 53.9 days (range: 4-204) and 35.7 days (3-6) for new and existing patients, respectively.…”
Section: Results Synthesismentioning
confidence: 99%
“…Standardizing the allotment of nursing hours optimizes availability of this scarce resource. Variations across state lines impact access to pediatric home care nursing, home care nursing hours, and contributes to healthcare disparities (Rasooly et al, 2020). Proposals suggest there should be federal standards for Medicaid home-based services (Ollove, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…care nursing, which may contribute to healthcare disparity (Rasooly et al, 2020). Currently no standard exists for prescribing pediatric nursing hours based on the medical complexity of the patient (Sobotka et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies can be used to provide an important beginning but reveal little about the actual quantity of HNC use. An approach to filling that knowledge gap is provided in this month's issue of Pediatrics by Rasooly et al, 5 who assessed the use of HNC among CMC. Using a 4-year commercial data set that included actual payments for services, the team looked at whether patients received any home nursing services within 30 days of a hospital discharge and the number of days of nursing services for those receiving them.…”
mentioning
confidence: 99%